A Single-switch Bi-polar Triple Output Converter with Fuzzy Control - Suganthi K, Idris Hadi Salih, Ganesh Babu Loganathan, Sundararaman K (International Journal of Advanced Science and Technology, 2020)
Many applications require multi-output converters with boost and buck outputs and sometimes negative outputs also. Reducing the number of switches for the same number of outputs minimises hardware count, board space and cost and improves efficiency. Many times, the input voltage that is available is of a low value and which may have to be stepped up to a high value. Additionally some auxiliary outputs may also be required. This paper elaborates a topology to achieve a triple output converter with boost, buck and negative outputs and with only a single switch. The main output is of a high positive voltage and there are two auxiliary outputs, one positive and the other negative. The control aspects of such a converter with PI control and fuzzy control have been presented. The main positive output voltage is rigorously controlled with duty cycle adjustment. The auxiliary outputs are controlled by adjusting the switching. frequency. Comprehensive Matlab simulation results with PI and fuzzy control confirm the feasibility of such a scheme and its control.Keywords: Bi-polar, Fuzzy control, Multi-output, Single-switch, Triple-output.